Association between quality antenatal care and low birth weight in Rwanda: a cross-sectional study design using the Rwanda demographic and health surveys data - Gérard Uwimana; Mohamed Elhoumed; Mitslal Abrha Gebremedhin; Mougni Mohamed Azalati; Lin Nan; Lingxia Zeng (BMC, 2023)
Abstract Background Low birth weight (LBW) is an important factor influencing infant morbidity and mortality. Pregnant women should receive a variety of interventions during antenatal care (ANC) that are crucial in improving birth weight. ANC visits alone do not promise that women have received all recommended antenatal services. However, there are limited evidence of the relationship between ANC quality and LBW in Rwanda. Therefore, the purpose of this study was to assess the association between quality ANC and LBW along with the factors influencing LBW and how quality ANC affects LBW in Rwandan pregnant women. Methods The Demographic and Health Surveys (DHS) are cross-sectional, nationally representative household surveys that collect population, health, and nutrition. In this Study we used three waves of Rwanda Demographic and Health Surveys 2010,2014-5 and 2019-20. A total of 16,144 women aged 15 to 49 years who had live births in the five years preceding each survey were included in this study. A stratified two-stage sampling methods was used to select the participants. The first stage involves selecting clusters (villages) from a list of all clusters in the country. The second stage involves selecting households within each cluster. A survey adjusted for clusters at multiple level and a bivariate and multivariable logistic regression was used to estimate adjusted odds ratios(aOR) and 95% confidence intervals to assess the association between the outcome and independent variables. Results The utilization of a high-quality ANC increased slightly over the three survey years and LBW had a slow decline. Out of 5813 women;201(3.45%) had high-quality ANC in the 2010 survey, and out of 5813 newborns,180(3.10%) were LBW. Out of 5404 women;492(9.11%) had high-quality ANC in 2015, and out of 5404 newborns,151(2.79% were LBW). Out of 5203 women,776(14.92%) had high-quality ANC in the 2020 survey year, and out of the 5206 newborns,139(2.67%) were LBW. In multivariable analysis, at a borderline limit high quality ANC was negatively associated with LBW(aOR:0.67;95%CI:0.43,1.05) compared to low-quality ANC. Higher birth orders of the newborn were negatively associated with LBW (aOR:0.63;95%CI:0.49,0.82 and aOR:0.44;95%CI:0.32,0.61 for 2nd -3rd and 4th and above respectively) compared to 1st orders newborn. Newborns from rich households were less likely to experience LBW than those from poor households (aOR:0.71;95%CI:0.55,0.91). Female newborns were associated with an increase of LBW (aOR:1.43;95% CI:1.18,1.73) than male newborns. Conclusion The findings confirm the fundamental importance of a high-quality ANC on LBW. The findings could be utilized to develop monitoring strategies and assess pregnancy health assistance programs with a focus on LBW reduction.